2018
DOI: 10.1002/pon.4739
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual and religious coping and depression among family caregivers of pediatric cancer patients in Latin America

Abstract: Negative SRC was associated with depressive symptoms in FCs of pediatric cancer patients. Health professionals must be aware of the use of Negative SRC strategies in oncology care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 37 publications
1
33
0
12
Order By: Relevance
“…Furthermore, previous works have reported a positive relation between caregivers’ anxiety and children’s distress experienced during medical procedures 50102103. Longitudinal data have also shown a moderate to strong equivalency between the caregiver’s and the child’s experiences on emotional competence during treatment 104…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, previous works have reported a positive relation between caregivers’ anxiety and children’s distress experienced during medical procedures 50102103. Longitudinal data have also shown a moderate to strong equivalency between the caregiver’s and the child’s experiences on emotional competence during treatment 104…”
Section: Discussionmentioning
confidence: 94%
“…In another study, neither positive nor negative religious coping strategies were significantly related to the well-being of mothers of children with autism (Davis and Kiang 2018). Finally, Vitorino et al (2018) observed that negative religious coping was associated with depression among family caregivers of pediatric cancer patients, also after adjusting for sociodemographic variables and positive religious coping, which was unrelated to depression. However, positive reappraisal was not included in any of these studies.…”
Section: Discussionmentioning
confidence: 90%
“…Their family suffered from prolonged fear and sadness (Sudarji et al, 2016). Coping abilities and lower levels of depression in caregiver have a correlation with positive communication (Vitorino et al, 2018). By knowing the communication patterns of caregivers and the factors that influence them, more effective communication that may be attempted to improve outcomes in children (Jaser et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Study in Denpasar, Bali showed that Children with ALL who undergo treatment therapy showed coping strategies, including accepting responsibility, humor, wishful thinking, assistance seeking, behavioral management, direct action, emotional approach, denial, self-control, and self criticism (Damayanti et al, 2016). Studies showed that the coping skills in caregiver may affect child stress level (Vitorino et al, 2018). In addition, family factors have also been shown to be related to parental stress levels.…”
Section: Discussionmentioning
confidence: 99%